Rowing - Wychowanski, M.; Baca, A. (Modelling and simulation in sport and exercise, 2020)
Completely different modelling approaches for answering practical issues in the Sport of rowing are presented in the third chapter. On the one hand, methods from classical Newtonian mechanics are applied; on the other, the potential of data-driven models is assessed. Moreover, it is demonstrated that different factors have to be considered when assessing performance in a particular sport. In the case of rowing, the outcome of a competition is not only affected by the motion technique, which is the main focus of the chapter, but also by the athletes` physical features and the tactical behavior.